Metode PLS: Analisis Kinerja Karyawan melalui Kepuasan Kerja dan Komitmen Karyawan - Yuanita, Saskia; Budiastuti, Dyah (Binus Business Review, 2012)
Global challenges of the current causes increasing competition among national and international businesses. Under these conditions, the company realizes the importance of quality and efforts to enhance competitiveness by doing improvements consistently and continuously in order to meet customer and market needs. This study aims to examine the effect of the implementation of ISO 9001 quality management system onemployee performance, and the moderating effects of job satisfaction and employee commitment to the relationship between the application of ISO 9001:2008 quality management system on employee performance. The method used to analyze is Partial Least Square (PLS). The results show that the application of ISO 9001:2008 quality management system affects performance of employees with employee satisfaction and commitment as moderating variable that affect the relationship between the application of ISO 9001:2008quality management system on employee performance. Both variables, moderating employee satisfaction and commitment have positive parameter estimation, so that when the satisfaction and commitment of employees increase, it will give effect to the improvement of the implementation of the ISO 9001:2008 quality management system on employee performance.